MENAKAR KETAHANAN NASIONAL DALAM ERA GLOBAL DITINJAU DARI ASPEK IDEOLOGI - Bali Widodo; Yogi Nugraha (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2025)
ABSTRACT The attitude and behavior of some Indonesian citizens in recent times are felt to be much contrary to the ideology of Pancasila. This could be because the Indonesian state with the ideology of Pancasila is located between communist and liberal ideologies, where geographically the country of Indonesia is located between the Asian continent (some countries adhere to communist ideology) and Australia which has a liberal ideology. The purpose of the research is to find out the extent of the influence caused by the two major world ideologies on the life of the Indonesian nation. The data obtained in this study came from various sources of scientific articles and various literature relevant to the research topic as well as the results of the researcher's observations on attitudes and behaviors that occur in society. The results of the study show that there is a change in the attitude and behavior of some citizens towards communists and liberals. For this reason, it is necessary to strengthen national resilience in the ideological aspect in order to counteract the entry of external ideological influences that are not in line with the values of Pancasila. Keywords: Indonesia's National Resilience, Global Era, Pancasila Ideology